2007
DOI: 10.1515/jpem.2007.20.5.639
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotropin-Secreting Pancreatoblastoma

Abstract: We present a 3-year-old child with Cushing's syndrome due to an ACTH-secreting metastatic pancreatoblastoma. This malignancy is a rare cause of Cushing's syndrome, particularly at pediatric age. We describe her course including the use of ketoconazole to alleviate hypercortisolemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…[5][6][7][8] Including our case, 5 of such cancers have been documented, and their clinicopathologic features are summarized in Table 4. These aggressive carcinomas were found in the pediatric age group and showed a poor outcome, as shown in Figure 3.…”
Section: Acth-secreting Accmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] Including our case, 5 of such cancers have been documented, and their clinicopathologic features are summarized in Table 4. These aggressive carcinomas were found in the pediatric age group and showed a poor outcome, as shown in Figure 3.…”
Section: Acth-secreting Accmentioning
confidence: 99%
“…In children and adolescents, ectopic ACTH secretion associated with CS has also been reported in association with pancreatic acinar cell carcinoma (ACC) and pancreatoblastoma, [5][6][7][8] rare tumor types with morphologic features sometimes overlapping those of PanNETs 9 and, for this reason, representing a diagnostic challenge for pathologists. Only 4 single cases of ACTH-secreting ACCs and pancreatoblastomas have been reported previously.…”
mentioning
confidence: 99%
“…In the case reported by Li et al [ 35 ], the patient showed elevated CA19-9 and Cancer Antigen 125 levels[ 35 , 38 ]. Rarely adrenocorticotropic hormone can be secreted from the tumor[ 40 - 42 ].…”
Section: Laboratory/imaging Findingsmentioning
confidence: 99%
“…This occurrence, however, is uncommon in adults 9 , 10 . A small fraction of patients may present with a concomitant para-neoplastic Cushing syndrome, due to an inappropriate secretion of ACTH 1 , 11-13 .…”
Section: Pancreatoblastomamentioning
confidence: 99%